2019
DOI: 10.3889/oamjms.2019.223
|View full text |Cite
|
Sign up to set email alerts
|

Resistance Trend, Antibiotic Utilization and Mortality in Patients with E. coli Bacteraemia

Abstract: BACKGROUND: Incidence of bacteraemia and driving concerns about antibiotic resistance is increasing globally. Risk factors for developing antimicrobial resistance are antibiotic overuse, incorrect dosing and extended duration of administration. AIM: This study was conducted to examine the prescription and susceptibility pattern of antibiotics in bacteraemia patients with ESBL producing and Non-ESBL-producing E. coli and their correlation with mortality. METHODS: Data were collected from medical rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 35 publications
0
1
0
Order By: Relevance
“…Various authors showed different susceptibility patterns in their study. Nadiq IA & Najmi et al showed a susceptibility of 11.7% & 9.8% to ampicillin, respectively, in contrast to 100% resistance in our study 6,18 . Susceptibility to cefotaxime was comparable to a study conducted by Najmi and Nepal 18,14 .…”
Section: Resultscontrasting
confidence: 67%
“…Various authors showed different susceptibility patterns in their study. Nadiq IA & Najmi et al showed a susceptibility of 11.7% & 9.8% to ampicillin, respectively, in contrast to 100% resistance in our study 6,18 . Susceptibility to cefotaxime was comparable to a study conducted by Najmi and Nepal 18,14 .…”
Section: Resultscontrasting
confidence: 67%
“…In an Indian study, the rates of AMC resistance in ESBL-positive and ESBL-negative E. coli were 100 and 77.6%, respectively. 18 Studies on urine isolates of E. coli in Turkey have shown AMC resistance rates in ESBL-positive E. coli of 68.6 to 100%. 17 19 In our study, AMC resistance rates were 66.7 and 29.4% in ESBL-positive and ESBL-negative E. coli strains.…”
Section: Discussionmentioning
confidence: 99%